(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
ResearchÂ onÂ theÂ developmentÂ ofÂ botanicalÂ pesticidesÂ shouldÂ be developedÂ throughÂ newÂ methods,Â suchÂ asÂ byÂ inhibiting theÂ activityÂ ofÂ digestive enzymesÂ byÂ secondaryÂ metabolites.Â TheÂ aimÂ ofÂ thisÂ studyÂ wasÂ toÂ identify someÂ ofÂ potentialÂ plantsÂ asÂ aÂ sourceÂ ofÂ tannin-proteinÂ complexesÂ toÂ inhibit theÂ activityÂ ofÂ ï¡- amylase.Â TheÂ studyÂ ofÂ identificationÂ ofÂ potentialÂ plants producingÂ theÂ activeÂ ingredientÂ tannin-proteinÂ complexÂ wasÂ dividedÂ intoÂ three stages,Â 1)Â identificationÂ ofÂ potentialÂ plantsÂ producingÂ tannin,Â 2)Â isolationÂ of tannin-proteinÂ complexes,Â andÂ 3)Â inÂ vitroÂ testÂ ofÂ tannin-proteinÂ complexes effectÂ ofÂ theÂ ï¡-amylase activity.Â SomeÂ ofÂ the observedÂ plantsÂ wereÂ sidaguriÂ leaf (Sida rhombifolia), melinjo leaf (Gnetum gnemon), gamal leaf (Gliricidia sepium), lamtoroÂ leafÂ (LeucaenaÂ leucocephala) ,Â betelÂ nutÂ (ArecaÂ catechu) ,Â andÂ crude gambierÂ (UncariaÂ gambir) a sÂ aÂ source ofÂ tanninsÂ andÂ melinjoÂ seed wasÂ usedÂ as proteinÂ source.Â BetelÂ nutÂ andÂ melinjoÂ seedÂ wereÂ theÂ bestÂ sourceÂ ofÂ tannin-proteinÂ complex,Â tanninÂ contentÂ 1.77Â mgÂ TAE/mLÂ withÂ antioxidantÂ activityÂ ofÂ 90%, theÂ abilityÂ toÂ inhibitÂ theÂ activityÂ ofÂ ï¡-amylase byÂ 95%Â withÂ IC 50Â valuesÂ of 10 mg/mL. Key words: Tannin, protein, ï¡-amylase, botanical pesticides,Areca catechu, Gnetum gnemon.